Miejsce i rola polskiego rynku kapitałowego w kontekście założeń strategii "Agenda Warsaw City 2010" - Szefczenko, Rafał (The place and role of Polish capital market in the context of "The Agenda Warsaw City 2010", 2007)
The Polish capital market was set up in 1991. It is still developing and the main institution of this market is the Warsaw Slock Exchange. In March 2002 the Council of Ministers accepted ihe Strategy for the Development of the Polish Capital Market - Agenda Warsaw City 2010. This documents based on the Lisbon Strategy, which intends to deal with the low productivity and stagnation of economic growth in the EU, through the formulation of various policy initiatives to be taken by all EU member states. Strategic business goals of the Polish capital market addresses the following areas: to become the largest exchange in the region, to become a key element of the regional financial centre located in Warsaw, to achieve a 50% market capitalisation/GDP ratio and to become an important hub in the network of Central European exchanges. These guidelines can be very difficult to achieve, therefore it is necessary to supervise a lot of aspects of capital market. Following years will get us an answer that assumptions of Agenda Warsaw City 2010 could be successfully realized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 145-153